EFEK DIAMETER COIL, PERBANDINGAN JUMLAH LILITAN, JENIS COIL, PADA TRASMITTER RECEIVER TERHADAP EFISIENSI ENERGI TRANSFER WIRELESS TRANSFER ELECTRICITY DENGAN METODE DESAIN OF EXPERIMENT (DOE) - Winarso, Kukuh; Alfaris, Salman (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2016)
Wireless power transfer is an alternative distribution of electrical power without a physical relationship with the cable. In the study took a problem concerning the design series of receiver on transfer system power without wires that have not done research on the effect of its components such as the diameter of the coil, the ratio of the number of windings, and the type of coil. The components used as an experiment to determine the efficiency of energy transfer from the result electric power. The purpose of this study is used to determine whether the components or factors such as the diameter of the coil, the ratio of the number of windings, and the type of coil give effect to the energy transfer efficiency of the electrical power produced. Research conducted an experiment using a factorial design experiments 23 to solve this problem. Materials used and also used as a factor in the study include the diameter of the coil, the ratio of the number of windings, and coil types, and each factor has two levels. The experimental results showed that factors coil diameter, number of turns ratio and type of coil influence on the efficiency of energy transfer. Decision-making is seen from the results of the calculation of the value of F count greater than F table values.Â Keywords: Wireless Power Transfer, The Efficiency of Energy Transfer, Factorial